The Conservation Biology of the Sulawesi Crested Black Macaque Macaca nigra (Primates: Cercopithecidae): A Review of Current Knowledge and Future Research Priorities - Randi Syafutra (BIO PALEMBANICA, 2026)
The endemic Sulawesi Crested Black Macaque Macaca nigra Desmarest, 1822 is restricted to northeastern Indonesia and is classified as Critically Endangered (CR) due to habitat fragmentation, agricultural expansion, and bushmeat hunting. This review synthesizes recent literature on the species' genetics, ecology, health, and conservation through a structured search of major academic databases. The evidence indicates that M. nigra is an adaptable frugivore capable of adjusting its diet and activity patterns in response to habitat disturbance and climatic variation, although these behavioral shifts may incur ecological and physiological costs. The review also incorporates findings from introduced populations in the North Moluccas and ex situ conservation programs, providing a broader perspective on the species' conservation status. Recent surveys suggest population stabilization in well-protected areas, likely supported by long-term research and community engagement, while introduced populations may serve as valuable genetic reservoirs. Continued conservation will require multidisciplinary research, effective law enforcement, and community-based education to reduce human–wildlife conflict. Key research priorities include the genetic viability of introduced populations, the consequences of dietary plasticity, zoonotic disease dynamics, climate change impacts, and the long-term success of translocation programs.